Age Related Changes in Muscle Mass and Force Generation in the Triple Transgenic (3xTgAD) Mouse Model of Alzheimer’s Disease - Xu, Hongyang; Bhaskaran, Shylesh; Piekarz, Katarzyna M.; Ranjit, Rojina; Bian, Jan; Kneis, Parker; Ellis, Aubrey; Bhandari, Suyesha; Rice, Heather C.; Van Remmen, Holly (Frontiers in Aging Neuroscience, 2022)
Emerging evidence suggests that patients with Alzheimer’s disease (AD) may show accelerated sarcopenia phenotypes. To investigate whether pathological changes associated with neuronal death and cognitive dysfunction also occur in peripheral motor neurons and muscle as a function of age, we used the triple transgenic mouse model of AD (3xTgAD mice) that carries transgenes for mutant forms of APP, Tau, and presenilin proteins that are associated with AD pathology. We measured changes in motor neurons and skeletal muscle function and metabolism in young (2 to 4 month) female control and 3xTgAD mice and in older (18–20 month) control and 3xTgAD female mice. In older 3xTgAD mice, we observed a number of sarcopenia-related phenotypes, including significantly fragmented and denervated neuromuscular junctions (NMJs) associated with a 17% reduction in sciatic nerve induced vs. direct muscle stimulation induced contractile force production, and a 30% decrease in gastrocnemius muscle mass. On the contrary, none of these outcomes were found in young 3xTgAD mice. We also measured an accumulation of amyloid-β (Aβ) in both skeletal muscle and neuronal tissue in old 3xTgAD mice that may potentially contribute to muscle atrophy and NMJ disruption in the older 3xTgAD mice. Furthermore, the TGF-β mediated atrophy signaling pathway is activated in old 3xTgAD mice and is a potential contributing factor in the muscle atrophy that occurs in this group. Perhaps surprisingly, mitochondrial oxygen consumption and reactive oxygen species (ROS) production are not elevated in skeletal muscle from old 3xTgAD mice. Together, these results provide new insights into the effect of AD pathological mechanisms on peripheral changes in skeletal muscle.